2015
DOI: 10.1111/iep.12122
|View full text |Cite
|
Sign up to set email alerts
|

The protective properties of melatonin against aluminium‐induced neuronal injury

Abstract: Aluminium (Al) toxicity is closely linked to the pathogenesis of Alzheimer's disease (AD). This experimental study investigated the neuroprotective effect of melatonin (Mel; 10 mg/kg bwt) on aluminium chloride (AlCl3 ; 34 mg/kg bwt) induced neurotoxicity and oxidative stress in rats. Adult male albino Wistar rats were injected with AlCl3 for 7 days. The effect on brain structure, lipid peroxidation (LPO), nitric oxide (NO) levels, glutathione (GSH) content, antioxidant enzymes (SOD, CAT, GPx and GR), apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 31 publications
(51 reference statements)
3
19
0
Order By: Relevance
“…MEL directly neutralizes ROS and NO as well as other toxic reactants. Also, MEL inhibits pro‐oxidative enzymes such as NO synthase, lipid peroxidation, MPO, COX‐2 and PC content . These data and our investigation clearly show that MEL might cause nephroprotection by decreasing the oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…MEL directly neutralizes ROS and NO as well as other toxic reactants. Also, MEL inhibits pro‐oxidative enzymes such as NO synthase, lipid peroxidation, MPO, COX‐2 and PC content . These data and our investigation clearly show that MEL might cause nephroprotection by decreasing the oxidative stress.…”
Section: Discussionsupporting
confidence: 75%
“…MEL directly neutralizes ROS and NO as well as other toxic reactants. Also, MEL inhibits pro-oxidative enzymes such as NO synthase and lipid peroxidation [38,39]. In a recent study, it was shown that MEL attenuates oxidative stress of the retina in DR [40].…”
Section: Discussionmentioning
confidence: 99%
“…Increased mitochondrial oxidative damage has also been observed in early pathological events leading to neurodegeneration (Beal, 1996). Aluminum-induced enhanced ROS production has been shown to cause DNA damage and finally apoptotic cell death (Alolayan et al, 2015). Protecting mitochondria from oxidative damage should be an effective therapeutic strategy against aluminum-induced oxidative stress and ensuing apoptosis.…”
Section: Introductionmentioning
confidence: 99%